Evaluating the impact of a resident research program in general surgery - Allen, Laura; Vogt, Kelly; Mele, Tina; Ott, Michael; Leslie, Ken; Colquhoun, Patrick (Canadian Medical Education Journal, 2017)
Background: Programs of resident research have been found to improve research productivity. However, evidence of the success of these programs is lacking in a Canadian context. The objective of this study was to evaluate the impact of the introduction of a formal program of resident research at a single Canadian academic centre. Methods: Resident research activities were tracked over a 10-year period (Resident Research Day (RRD) presentations, abstract presentations, published articles). Activities were divided into pre (2002-2007) and post (2007-2012) resident research program implementation time frames. Differences in research productivity were compared between time frames. Surveys of resident attitudes towards research were administered prior to the program’s implementation in 2007, and following introduction of the resident research program in 2009 and 2015. Results: Overall, research productivity (abstracts, publications, and RRD presentations) increased between pre and post resident research program time periods, with a statistically significant increase in mean number of published abstracts. Resident attitudes towards research changed somewhat over time, with fewer residents supporting mandatory research in recent years. Conclusion: Implementation of a resident program of research resulted in a significant increase in research productivity. The setting of clear, modifiable, and achievable goals, as well as providing tools for research success, have contributed to the success of this program.